2015
DOI: 10.1155/2015/794601
|View full text |Cite
|
Sign up to set email alerts
|

Recent Trends in Preparation of Poly(lactide‐co‐glycolide) Nanoparticles by Mixing Polymeric Organic Solution with Antisolvent

Abstract: In recent years, there have been a plethora of nanoengineering approaches for the development of poly(lactide-co-glycolide) (PLGA) nanoparticulate carrier systems. However, overlooking the multifaceted issues in the preparation and characterization of PLGA-based nanoparticles, many reports have been focused on theirin vivobehaviors. It is imperative to fully assess technological aspects of a nanoencapsulation method of choice and to carefully evaluate the nanoparticle quality. The selection of a nanoencapsulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 201 publications
2
105
0
1
Order By: Relevance
“…It is an emulsification process that requires low energy and no surfactant (71,92,100). The effect A c c e p t e d M a n u s c r i p t 11 can be explained as the quick coupling of the hydrophobic compound in the "ouzo" or metastable region between the spinoidal and binoidal limits shown in a ternary phase diagram.…”
Section: Ouzo Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an emulsification process that requires low energy and no surfactant (71,92,100). The effect A c c e p t e d M a n u s c r i p t 11 can be explained as the quick coupling of the hydrophobic compound in the "ouzo" or metastable region between the spinoidal and binoidal limits shown in a ternary phase diagram.…”
Section: Ouzo Effectmentioning
confidence: 99%
“…92). The precipitation of the polymer is given by the increase of diffusion of the solvent, adding a larger amount of nonsolvent, or by evaporating the solvent (21).…”
mentioning
confidence: 99%
“…A w/o microemulsion method with binary organic phase was used in this study to improve the loading efficiency [51]. This method provides high encapsulation efficiencies toward hydrophilic drugs [52]. Qian et al reported a similar system for the loading of validamycin (water-soluble antibiotics) into CaCO 3 nanoparticles with loading efficiency of 19.3% [12].…”
Section: Determination Of Micsmentioning
confidence: 99%
“…The solvent evaporation technique has been used extensively to prepare polymeric NPs containing different agents. Single solvent evaporation is a platform easily adapted with high-entrap efficiency for hydrophobic compounds (Edel Sah and Hongkee Sah 2015). However, the preparation conditions should be optimized based on the physicochemical properties of encapsulated drugs.…”
Section: Discussionmentioning
confidence: 99%